2018
DOI: 10.1108/nfs-02-2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of health professionals about probiotic use in Ahmedabad, India

Abstract: Purpose The purpose of this study was to assess the knowledge, attitude and practice about probiotic use among health professionals of Ahmedabad, India. Design/methodology/approach A structured questionnaire was prepared. The questionnaire consisted of 12 close-ended questions related to definition, mechanism of action, safety consideration, health benefits, sources and four questions to assess their attitude and practice about probiotics. Total 267 healthcare professionals were requested to fill the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 15 publications
4
32
2
Order By: Relevance
“…More than 80% of pharmacists, allied health professionals, medical doctors, dentists, and other health professionals identified the correct definition of probiotics, whereas the corresponding percentage for registered nurses and midwives was 75. In the study by Soni et al [23], the knowledge of probiotics among health students of various disciplines also differed significantly, with approximately 93% of participants being aware of the term ‘probiotics’ and about 80% of them defining it correctly. A similar study in [32] also reported a low level of knowledge of probiotics among university students and emphasized the need for education about the nutritional and health benefits of fermented dairy products, especially those containing probiotics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More than 80% of pharmacists, allied health professionals, medical doctors, dentists, and other health professionals identified the correct definition of probiotics, whereas the corresponding percentage for registered nurses and midwives was 75. In the study by Soni et al [23], the knowledge of probiotics among health students of various disciplines also differed significantly, with approximately 93% of participants being aware of the term ‘probiotics’ and about 80% of them defining it correctly. A similar study in [32] also reported a low level of knowledge of probiotics among university students and emphasized the need for education about the nutritional and health benefits of fermented dairy products, especially those containing probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…We found a statistically significant difference in the knowledge of the correct definition of probiotics in favor of females (χ 2 = 4.853; p = 0.028). Other studies have reported different results, ranging from non-significant differences [23,34] to male participants having a higher knowledge [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The questions were modeled and changed based on those used in previously published studies on the knowledge of probiotics. 8 The questionnaire consists of 15 items in 3 subscales: demographics and practice characteristics (5 items); de nition and knowledge of probiotics (9 items); and source of probiotics -related information (1item). The survey includes multiple-choice questions.…”
Section: Questionnaire Instrumentmentioning
confidence: 99%